EXPLORING THE POSSIBILITIES OF INCREASING THE CONTACT COMFORT BY WOODEN MATERIALS – TACTILE INTERACTION OF MAN AND WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
The paper deals with the problematic of contact comfort as a part of a user-centred de-sign. Contact comfort consist of a combination of balanced surface temperature, heat trans-mission, surface roughness, surface elasticity/hardness, sorption activity of the surface in terms of vapor absorbance. All these parameters are measurable and it is possible to optimize them with the aim to achieve solutions that are providing higher contact comfort.Different wood based materials and wood species with different types of surface finish-ing were investigated by using a test chair. The current paper presents the methodology and results of this study. It could be shown that wooden surfaces are assessed more positive by the probands than aluminium and polypropylene.